Empowering Agriculture: Unveiling the Paddy Knowledge Portal's User Requirements and Use Cases - Wan Ishak, Wan Hussain; Mat Yamin, Fadhilah; Abu, Noor Hidayah; Othman, Zakirah; Suroso, Arif Imam; Dewi, Febriantina; Rizky, Lokita; Kamilla, Khariyah; Tandra, Hansen; Md. Kassim, Normalini (Journal of Advanced Research Design, 2025)
Agriculture, a pivotal sector sustaining human life, confronts diverse challenges that demand innovative solutions for enduring viability. Paddy cultivation, an integral facet of global agriculture, grapples with issues affecting productivity, sustainability, and economic feasibility. This paper underscores the significance of knowledge management in tackling these challenges and introduces the Paddy Knowledge Portal as a transformative tool. The Paddy Knowledge Portal, functioning as a centralised hub for rice cultivation information, caters to a varied audience, including farmers, researchers, and experts. Leveraging knowledge management principles, the portal facilitates the dissemination of best practices, research findings, and cutting-edge technologies. By encouraging active user participation, it cultivates a collaborative environment essential for continuous learning and growth. This paper discusses the user requirements and use cases for the knowledge portal. The user requirements were compiled from two primary sources: a literature review and direct stakeholder feedback. The delineation of user requirements and associated use cases serves as a valuable reference for researchers. The Paddy Knowledge Portal will emerge as a pivotal resource, contributing to the sustainability and resilience of paddy cultivation amid the dynamic landscape of agriculture.